EVALUASI PUTUSAN PENGADILAN TINDAK PIDANA EKONOMI DI INDONESIA: STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 78 K/PID.SUS/2022 - Aulia, Safira Rahma (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Law enforcement against economic crimes is a crucial aspect in maintaining the stability and integrity of a country's economy. This article aims to evaluate the Supreme Court Decision Number 78 K/Pid.Sus/2022, which is one of the important decisions regarding economic crimes in Indonesia. This research uses a normative juridical method with a qualitative approach to analyze the legal considerations in the decision and its impact on law enforcement and prevention of economic crimes in Indonesia. The results of the analysis show that this decision was based on comprehensive consideration of the evidence, witnesses and legal arguments presented. However, there are several weaknesses in the decision that can affect legal certainty and a sense of justice for the parties involved. The impact of this decision is not only felt by the defendant, but also has broad implications for the legal system and economic regulations in Indonesia. This article concludes that although Supreme Court Decision Number 78 K/Pid.Sus/2022 has fulfilled most of the principles of justice, further efforts are still needed to improve regulations and law enforcement for economic crimes. Recommendations are given to policy makers and law enforcement officials to increase cooperation and coordination in order to strengthen the justice system and prevent the occurrence of economic crimes in the future